2018
DOI: 10.1097/meg.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus treatment by direct-acting antivirals in successfully treated hepatocellular carcinoma and possible mutual impact

Abstract: Treatment of HCV in successfully treated HCC is feasible, with the best results achieved using multiple direct-acting antivirals and RBV; a high rate of HCC recurrence was observed, especially within the first 6 months of treatment initiation (ClinicalTrials.gov no: NCT02771405).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…TACE. More than 80% of these patients developed recurrence within 6 months of treatment initiation [24].…”
Section: Studies That Suggested a Link Between Hcc Development/recurrmentioning
confidence: 99%
“…All these factors could explain, from a mechanistic point of view, the phenomena of ‘time association between DAA treatment and HCC recurrence’ reported by our group and the Italian group [40,41,42]. Several authors validated these data even though it was not reported in the conclusion of their manuscripts (Table 1 [40,41,43,44,45,46,47,48,49,50,51,52,53,54] adapted from [55]). In this regard, our original manuscript was focused on patients who achieved complete response (CR) without non-characterized nodules (no-ChN) to avoid an over-interpretation of the HCC recurrence rate.…”
Section: Time Association Between Daa Treatment and Hcc Recurrencementioning
confidence: 55%